Bridging Heritage and Modernization: Contextual Project-Based Learning for Indonesian Papuan Student Identity Formation - Febriyani Sulistyaningsih; Harun Joko Prayitno; Djalal Fuadi (Didaktika: Jurnal Kependidikan, 2025)
This study examines the implementation and impact of the Papuan Cultural Studies and Modernization (PBPM) contextual project-based learning model at Sekolah Anak Indonesia (SAI), a boarding school serving indigenous Papuan students. The background of this research is Papua’s low Human Development Index, largely due to educational disparities and culturally unresponsive curricula. This study aims to analyze PBPM’s implementation, its effects on regional identity, motivation, and student engagement, as well as key enabling and inhibiting factors. A qualitative case study design was used, with purposive sampling involving 32 students, 10 teachers, and 4 foundation structural members. Data collection involved semi-structured interviews, observations conducted in classrooms, and analysis of relevant documents, which were then examined using thematic analysis. The findings reveal that institutional support, curriculum flexibility, and community involvement are critical to PBPM’s success. The model strengthens students’ cultural identity, motivation, and practical skills, but faces challenges such as a shortage of culturally sensitive teachers, language barriers, and limited resources. PBPM offers an innovative framework that can be adapted to other indigenous educational contexts, with future research prospects including the development of bilingual instruction and alumni tracking.